Thiol chitosan-wrapped gold nanoshells for near-infrared laser-induced photothermal destruction of antibiotic-resistant bacteria. (1st December 2019) - Manivasagan, Panchanathan; Khan, Fazlurrahman; Hoang, Giang; Mondal, Sudip; Kim, Hyehyun; Hoang Minh Doan, Vu; Kim, Young-Mog; Oh, Junghwan
Graphical abstract: Highlights: Thiol chitosan-wrapped gold nanoshells (TC-AuNSs) are used as photothermal agents. TC-AuNSs possess good biocompatibility and outstanding photothermal properties. TC-AuNSs-treated bacteria were completely destroyed within 5 min of laser irradiation. TC-AuNSs is highly efficient and fast killing and prevent bacterial regrowth. Abstract: Developing new antibacterial nanomaterials and novel therapeutic strategies for the destruction of human pathogenic bacteria that cause infectious diseases is becoming more crucial, because infections caused by antibiotic-resistant bacteria are becoming more and more difficult to be effectively cured with commercially available antibiotics. In this study, we successfully developed new thiol chitosan-wrapped gold nanoshells (TC-AuNSs) as an antibacterial agent for the near-infrared (NIR) laser-triggered photothermal destruction of antibiotic-resistant pathogens, such as Gram-positive bacteria ( Staphylococcus aureus ) and Gram-negative bacteria ( Pseudomonas aeruginosa and Escherichia coli ), owing to their high water solubility, biocompatibility, strong NIR absorption, and outstanding photothermal properties. More interestingly, TC-AuNSs (115 μg/mL) were capable of completely destroying S. aureus, P. aeruginosa, and E.coli within 5 min of NIR laser irradiation, and no bacterial growth was detected on the tryptic soy agar (TSA) plate after 48 h of laser irradiation, indicating that TC-AuNSs along with laser irradiation are highly efficient and can kill bacteria quickly and prevent bacterial regrowth. We believe that TC-AuNSs deserve much more attention as an antibacterial agent, to be used in effectively combating pathogenic bacteria associated with public health problems and monitoring of environmental pollution for hygiene and safety.